Deteksi Kadar Alkohol Menggunakan Sensor MQ3 Berbasis Website - Ismail, Munaf; Marwanto, Arief; Haddin, Muhamad (P3M Politeknik Negeri Cilacap, 2021)
According to the Head of the Indonesian National Police (Kapolri) General Idham Azis, the number of deaths from accidents that occurred in 2019 reached 23,530. A total of 40% of the deaths from traffic accidents are caused by human error and the influence of alcohol. The high number of deaths from traffic accidents due to the influence of alcohol is a concern for all of us. Excessive alcohol consumption is dangerous when driving because consuming alcohol will affect a person's temperament and worsen driving behavior by reducing awareness, leading to accidents. A system that is able to detect the alcohol level of a vehicle driver that can be monitored anywhere is needed, as information to alert motorists to the influence of alcohol in order to prevent traffic accidents online and on a web-based basis. Using the MQ-3 sensor for alcohol detection and the ESP8266 processor in WeMos WiFi. Â The average percentage error in the measurement of the measured sample was found to have an error value of: 3.6%. Research has also succeeded in reading alcohol levels through websites.